Food and Feeding Habits of Osteochilus vittatus Valenciennes, 1842 and Barbodes binotatus Valenciennes, 1842, in Tamblingan Lake, Bali - Sathyananta, Kadek Prayuda; Pertami, Nyoman Dati; Parawangsa, I Nyoman Yoga; Surya Pramana, Made Arya (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Tamblingan Lake is the smallest lake in Bali and is inhabited by various species of fish, which are from the Cyprinidae family, namely bonylip barb and spotted barb. Information regarding the food and feeding habits of bonylip barb and spotted barb fish in Tamblingan Lake is unavailable. This study aims to determine and analyze the food and feeding habits of bonylip barb and spotted barb fish in Tamblingan Lake. Fish sampling was conducted from January to June 2019 in Tamblingan Lake using modified gill nets with a net size of 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 cm. Fishing was carried out at five stations with water characteristics representing the condition of Tamblingan Lake. Bonylip barb fish obtained during the study comprised 216 individuals, while the Spotted barb had 180 individuals. The average value of the relative intestinal length of bonylip barb fish ranged from 4.34 to 5.53, while that of the spotted barb fish was 0.89 to 1.30. The average value of the gastric fullness index of film fish ranges from 1.34 to 4.77, while the spotted barb is 0.32 to 0.42. The total IRI value of bonylip barb fish food in Tamblingan Lake is 924.32, while the spotted barb is 1,232.62, with the highest IRI value in both species coming from plankton. Bonylip barb and spotted barb in Tamblingan Lake developed a generalist feeding strategy with plankton food groups (planktivorous). Information related to these fishes can be used to formulate fish resource management in Tamblingan Lake.